1970
DOI: 10.3329/bjb.v37i1.1560
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between seed yield and yield components in narbon bean (Vicia narbonensis L.) by path analysis

Abstract: Results of correlation analysis indicated that seed yield in narbon bean (Vicia narbonensis L.) was correlated positively with harvest index, biological yield, weight, number of seed and number of pod per plant and also plant height and number of plant per m 2 . Path coefficient analyses revealed that harvest index and biological yield had higher positive direct effects on seed yield than other variables. Stepwise multiple regression analysis showed that 95.1% of total variation in seed yield could be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…as the most promising source of quality breeding material (Berger et al 2002). A correlation analysis based upon the performance of the Turkish local landraces of Narbonne vetch indicated that grain yield was positively correlated with number of plants per m 2 , plant height, number of pods per plant, number of grains per plant and harvest index (Türk et al 2008). The results of a field trial (Fig.…”
Section: Narbonne Vetch (Vicia Narbonensis L)mentioning
confidence: 93%
“…as the most promising source of quality breeding material (Berger et al 2002). A correlation analysis based upon the performance of the Turkish local landraces of Narbonne vetch indicated that grain yield was positively correlated with number of plants per m 2 , plant height, number of pods per plant, number of grains per plant and harvest index (Türk et al 2008). The results of a field trial (Fig.…”
Section: Narbonne Vetch (Vicia Narbonensis L)mentioning
confidence: 93%
“…Correlation coefficient analyses usually show relationships among independent traits and the degree of linear relation between these characters (Turk et al 2008). Consequently, these interrelationships with regards to sign and magnitude were found to be different when path analyses were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Kara ve Akman (2007) found out positive and important relationships between grain yield and plant length, 1000 grains weight and hectolitre in wheat in their study. Turk et al (2008) proposed harvest index and biological yield to be the primary selection criteria to improve seed yield in narbon vetch. In the study conducted with narbon vetch (Seydosoglu et al, 2014), in genotypes plant length was 44.2-61.3 cm, main stem length was 70.8-92.5 cm, broad bean number in plant was 9.6-14.6, green plant yield was 2207.0-4097.8 kg da -1 , dry plant yield was 526.2-935.2 kg da -1 and seed yield was 267.7-431.6 kg da -1 .…”
Section: Resultsmentioning
confidence: 99%
“…A positive relationship was found between grain yield and plant lentgh, biological yield, 1000 grains weight and broad bean length, the number of sub branches and the grain number in broad bean; a negative relationship was found between grain yield and the number of broad beans in plant (Buyukburç and Iptas, 2001); it was also found that there was a high and positive relationship between grain yield and harvest index and biological yield and plant length (Turk et al, 2008).…”
Section: Introductionmentioning
confidence: 94%